Sports Nutrition Management - Suzuki, Shihoko (The Japanese Journal of Nutrition and Dietetics, 2012)
In the field of sports and health promotion, nutrition management cannot be conducted using the same approach as those already established for nutrition care and management in other fields. This is attributable to differences between the 2 types of management with respect to the purpose of management, the period of management, subjects, the need for an action plan, and the evaluation items. Therefore, a new approach was devised for sports nutrition management. The process involved in this management was as follows: First, the purpose and period of management were determined; subsequently, the subjects were chosen via screening, and personal support (personal management) was ensured for each subject. After personal support was achieved, the nutrition management was evaluated, including the results pertaining to personal support for all subjects. Personal support was ensured in the following order: assessment, setting of personal aims, drafting a support plan, enforcement of the support plan, monitoring, and personal evaluation. The analysis showed that high-quality effective nutritional management could be achieved in the case of sports nutrition management because the Japanese women's national softball team won the gold medal at the 2008 Olympics Games in Beijing. Therefore, sports nutrition management was introduced as a nutrition management system in the field of sports and health promotion in Japan.